Impact of anaemia and the effect of empagliflozin in heart failure with reduced ejection fraction: findings from EMPEROR‐Reduced. (9th January 2022) - Ferreira, João Pedro; Anker, Stefan D.; Butler, Javed; Filippatos, Gerasimos; Iwata, Tomoko; Salsali, Afshin; Zeller, Cordula; Pocock, Stuart J.; Zannad, Faiez; Packer, Milton
Abstract : Aims: Anaemia is frequent among patients with heart failure (HF) and reduced ejection fraction (HFrEF) and is associated with poor outcomes. Sodium–glucose co‐transporter 2 inhibitors (SGLT2i) increase haematocrit and may correct anaemia. This study aims to investigate the impact of empagliflozin on haematocrit and anaemia, and whether anaemia influenced the effect of empagliflozin in EMPEROR‐Reduced. Methods and results: Mixed‐effects models and survival analysis. A total of 3726 patients (out of 3730) had baseline haematocrit values, 3013 (81%) had no anaemia and 713 (19%) had anaemia. Patients with anaemia were older (70.4 vs. 66.0 years), had lower body mass index (26.6 vs. 28.2 kg/m 2 ), lower estimated glomerular filtration rate (54.2 vs. 63.9 ml/min/1.73 m 2 ), and higher N‐terminal pro‐B‐type natriuretic peptide (2362 vs. 1800 pg/ml). Compared to patients without anaemia, those with anaemia had 1.5 to 2.5‐fold higher rates of cardiovascular and all‐cause mortality, total HF hospitalizations, and kidney composite outcomes. The effect of empagliflozin to reduce the primary composite outcome of cardiovascular death or HF hospitalizations, total HF hospitalizations, and kidney composite outcome was not modified by baseline anaemia status (interaction p > 0.1 for all). Compared to placebo, empagliflozin rapidly (as early as week 4) increased haematocrit and haemoglobin and reduced the rates of new‐onset anaemia throughout the follow‐up (22.6% in placebo vs. 12.3% in empagliflozin; hazard ratio 0.49, 95% confidence interval 0.41–0.59; p < 0.001). Conclusions: Anaemia was associated with poor outcomes. Empagliflozin reduced new‐onset anaemia throughout the follow‐up and improved HF and kidney outcomes irrespective of anaemia status at baseline. Abstract : Effect of empagliflozin on new‐onset anaemia. Among patients without anaemia at baseline (1511 in the placebo group and 1502 in the empagliflozin group), the number patients with new‐onset anaemia was 341 (22.6%) in the placebo group and 184 (12.3%) in the empagliflozin group, corresponding to a hazard ratio of 0.49 (95% confidence interval 0.41–0.59; p < 0.001).